Diagnosis and management of face presentation: a case report featuring an innovative diagnostic approach and fetal spinal protection technique - Cui, Ying; Yi, Jingjing; Xiao, Birong; Chen, Chen (Frontiers in Medicine, 2025)
We report the case of a 40 + 2-week pregnant woman who experienced spontaneous rupture of membranes at the end of the first stage of labor, followed by palpation of an irregular, soft tissue mass at the presenting part. Initial examination suggested a breech presentation; however, a definitive diagnosis could not be established by palpation alone. Using a vaginal dilator to directly visualize the presenting part, we confirmed the diagnosis of face presentation and achieved a successful vaginal delivery, with favorable outcomes for both the mother and the neonate. By reviewing the patient’s medical history, diagnostic process, and delivery progression, we identified the causative factors and underlying delivery mechanism in this case. We propose a simple and practical diagnostic approach and share a novel obstetric technique for fetal spinal protection during delivery. Furthermore, we underscore the importance of multidisciplinary collaboration in the management of facial presentation to optimize maternal and neonatal outcomes, thereby offering a reference for the clinical management of similar cases.